COSO-BASED INTERNAL CONTROL IN INDONESIAN ZAKAT INSTITUTIONS - Lestari, Wiji; Amrizal, (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
Effective internal controls are essential for organizations, especially zakat management agencies, to ensure that operations run efficiently, financial reports are trustworthy, and compliance with regulations and policies can be met. This study aims to analyze the implementation of COSO-based internal control in philanthropic institutions, especially in the Jambi area, Indonesia. The methodology of this study uses a qualitative descriptive approach with a case study on BAZNAS in Tanjung Jabung Barat Regency, Jambi, Indonesia. Data were obtained through interviews, observations, and documentation. Interviews were conducted with various relevant parties, including BAZNAS management and staff, to gain an in-depth understanding of the implementation of COSO-based internal controls. The results of the study show that BAZNAS of Tanjung Jabung Barat Regency has implemented most of the components of COSO-based internal control, namely the control environment, risk assessment, control activities, information and communication, and monitoring. However, there are elements that have not been implemented structurally, namely the formation of an internal audit team from BAZNAS itself. In addition, increased compliance in the writing of financial statements in accordance with 109 accounting standards is also needed.